2020
DOI: 10.1272/jnms.jnms.2020_87-403
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Infection after Colorectal Surgery: Subanalysis of Data from the 2015 Japan Postoperative Infectious Complications Survey

Abstract: Background: Most surveillance programs for postoperative infection focus on surgical site infections (SSI). However, remote infections, as postoperative infections, are of emerging clinical importance. We investigated the incidence of both SSI and remote infection following colorectal surgery by performing a subanalysis of a multicenter survey after gastrointestinal surgery. Methods: From September 2015 to March 2016, 1724 patients underwent colorectal surgery in 28 affiliated institutions in Japan. We retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This study revealed that the age, BMI, and the number of patients with diabetes, levels of serum TNF-α, IL-6 and PCT in the infection group were significantly higher than those in the non-infection group, suggesting that patients with postoperative incision infection had more serious inflammatory reactions, the age, obesity, and diabetes may increase the incidence of postoperative incision infections in patients with lumbar fusion. This may be related to the following reasons: (I) with an increase in age, the physical function and immune function of the patient gradually decreases, thereby increasing their risk of postoperative surgical incision infections (12); (II) patients with obesity have a thick layer of subcutaneous fat, and the postoperative wound aseptic gauze may be soaked by oily fat solutions, thereby increasing the postoperative wound infection rate (13); and (III) diabetes can increase the risk of vascular injury, incision tissue ischemia and hypoxia, and further aggravate postoperative incision infections (14,15). After infection, the levels of various inflammatory factors, including IL-6 and TNF-α, will increase, resulting in inflammatory cascade reactions, and high levels of inflammatory factors can aggravate oxidative stress injury and accelerate the infection process of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the age, BMI, and the number of patients with diabetes, levels of serum TNF-α, IL-6 and PCT in the infection group were significantly higher than those in the non-infection group, suggesting that patients with postoperative incision infection had more serious inflammatory reactions, the age, obesity, and diabetes may increase the incidence of postoperative incision infections in patients with lumbar fusion. This may be related to the following reasons: (I) with an increase in age, the physical function and immune function of the patient gradually decreases, thereby increasing their risk of postoperative surgical incision infections (12); (II) patients with obesity have a thick layer of subcutaneous fat, and the postoperative wound aseptic gauze may be soaked by oily fat solutions, thereby increasing the postoperative wound infection rate (13); and (III) diabetes can increase the risk of vascular injury, incision tissue ischemia and hypoxia, and further aggravate postoperative incision infections (14,15). After infection, the levels of various inflammatory factors, including IL-6 and TNF-α, will increase, resulting in inflammatory cascade reactions, and high levels of inflammatory factors can aggravate oxidative stress injury and accelerate the infection process of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic leakage is one of the most serious complications of lower anterior resection for rectal cancer. That may cause perioperative death and poor prognosis 1 , 2 , and is also considered to be a major influential factor on organ/space surgical site infection that occurs in approximately 5% of colorectal surgery 3 . In addition, it sometimes requires a permanent stoma, which remarkably worsens the patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…To explain, the potential impact of gastrointestinal surgery on the normal func- tioning of the gastrointestinal tract can lead to temporary impairment of gastric function and a decrease in digestive function. This can result in gastric reflux, where refluxed material is aspirated into the airway, potentially leading to pulmonary infections [12].…”
Section: Discussionmentioning
confidence: 99%